2014
DOI: 10.1103/physrevb.90.125433
|View full text |Cite
|
Sign up to set email alerts
|

Induced work function changes at Mg-doped MgO/Ag(001) interfaces: Combined Auger electron diffraction and density functional study

Abstract: The properties of MgO/Ag(001) ultrathin films with substitutional Mg atoms in the interface metal layer have been investigated by means of Auger electron diffraction experiments, ultraviolet photoemission spectroscopy, and density functional theory (DFT) calculations. Exploiting the layer-by-layer resolution of the Mg KL23L23 Auger spectra and using multiple scattering calculations we first determine the inter-layer distances as well as the morphological parameters of the MgO/Ag(001) system with and without Mg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Depending on the oxygen partial pressure and the substrate temperature employed during the reactive deposition of ultra-thin Mg oxide films, the p-type Schottky barrier has been tuned over 0.7 eV [125]. These remarkable variations of the Schottky barrier were ascribed to the decrease of the silver work function induced by the Mg enrichment of the substrate surface region (associated to the formation of a Mg-Ag alloy) when Mg is evaporated in oxygen-poor conditions or at high substrate temperatures [125,126]…”
Section: Band Alignment Across the Interfacementioning
confidence: 99%
“…Depending on the oxygen partial pressure and the substrate temperature employed during the reactive deposition of ultra-thin Mg oxide films, the p-type Schottky barrier has been tuned over 0.7 eV [125]. These remarkable variations of the Schottky barrier were ascribed to the decrease of the silver work function induced by the Mg enrichment of the substrate surface region (associated to the formation of a Mg-Ag alloy) when Mg is evaporated in oxygen-poor conditions or at high substrate temperatures [125,126]…”
Section: Band Alignment Across the Interfacementioning
confidence: 99%
“…In addition, PT confirms an integer charge transfer, which would be expected to result from tunneling [15]. However, using the ability to tune the MgO(100)/Ag(100) work function after MgO film growth (Φ MgO ) by changing the composition at the dielectric-metal interface without changing its surface [16][17][18][19], it has been recently shown that two distinct adsorption regimes exist [20]. On films with a high Φ MgO , all molecules in the ML remain neutral, whereas on a low-Φ MgO substrate, charge transfer is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The metal-induced gap states at the metal/oxide interface, the oxide band gap, and a surface core exciton involving an image-potential state of the vacuum are revealed through resonant Auger spectroscopy of the Mg KL 23 (001) is a model system of the metal/oxide interface at the ultrathin limit. Although the structure and the growth mechanism [4][5][6][7][8][9], as well as changes in electronic properties associated with depositing ultrathin films of MgO on Ag(001), have been investigated [10][11][12][13][14][15][16][17], capturing the physical nature of such a mixed system, and in particular of the interfaces, remains challenging.In resonant auger spectroscopy (RAS), the Auger process can be very different from that occurring with photon energies far above absorption thresholds [18]. Sub-lifetime narrowing effects [19], as well as strong modulations in Auger signals [20], can occur.…”
mentioning
confidence: 99%
“…In this context, MgO/Ag(001) is a model system of the metal/oxide interface at the ultrathin limit. Although the structure and the growth mechanism [4][5][6][7][8][9], as well as changes in electronic properties associated with depositing ultrathin films of MgO on Ag(001), have been investigated [10][11][12][13][14][15][16][17], capturing the physical nature of such a mixed system, and in particular of the interfaces, remains challenging.…”
mentioning
confidence: 99%
See 1 more Smart Citation